Pendampingan Kalibrasi Arah Kiblat Bagi Imeum Chik di Provinsi Aceh: Qibla Direction Calibration Assistance for Imeum Chik in Aceh Province - Machzumy, Machzumy; Mahli, Mahli (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Determining the qibla direction is a topic that also captures public attention. Issues arise among the public when rechecking the qibla direction, leading to various doubts, especially among the people of Aceh province. Based on initial investigations by the facilitator regarding the qibla direction of several mosques in Aceh province, it was found that, on average, the qibla direction of mosques deviates from the direction of the Kaaba. The research problem formulated is: "What form of facilitation is provided to the imam chik in calibrating the qibla direction in Aceh province?" The facilitation method used is the Broad Based Education (BBE) method. The facilitation takes place at four mosques in Aceh province, with the imam chik as the subject. The result are the imeum chik can learn and understand the steps involved in using a theodolite to calibrate the direction of the qibla. They also become aware that the mosques have experienced an average deviation 5.320 of qibla direction. Furthermore, with the assistance provided through of using a theodolite, the imeum chik act as mediators to help the society understand the importance and accuracy of qibla calibrations.